2019
DOI: 10.1111/gwat.12862
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Contamination in Karst Groundwater Systems

Abstract: Groundwater in karst aquifers constitutes about 25% of drinking water sources globally. Karst aquifers are open systems, susceptible to contamination by surface‐borne pollutants. In this study, springs and wells from two karst aquifers in Illinois, USA, were found to contain microplastics and other anthropogenic contaminants. All microplastics were fibers, with a maximum concentration of 15.2 particles/L. The presence of microplastic was consistent with other parameters, including phosphate, chloride and tricl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
5
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 339 publications
(164 citation statements)
references
References 32 publications
6
119
5
5
Order By: Relevance
“…Smaller particles are more likely to move horizontally and vertically. Panno et al () recently detected microplastics, exclusively fibers, up to 15.2 particles L ‐1 in 16 of 17 groundwater samples from two karst aquifers in Illinois (USA). They hypothesized these microplastics may have been derived from drainage from private septic systems.…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller particles are more likely to move horizontally and vertically. Panno et al () recently detected microplastics, exclusively fibers, up to 15.2 particles L ‐1 in 16 of 17 groundwater samples from two karst aquifers in Illinois (USA). They hypothesized these microplastics may have been derived from drainage from private septic systems.…”
Section: Microplastics In the Indoor And Terrestrial Environmentmentioning
confidence: 99%
“…Microplastic morphological characteristics (shape, texture, and size) may influence toxicological outcomes, for example, controlling if it is translocated in the tissues, blocks the digestive tract, or irritates or lacerates tissues, resulting in abnormalities or increasing susceptibility to infectious diseases. Growing research suggests that microfibers are a prevalent form of plastic pollution in the environment (Güven et al, ; Panno et al, ; Michielssen et al, ). Their dimensions may present novel risks, as they are more likely to penetrate or otherwise irritate tissues.…”
Section: Microplastic Uptake and Consequences In Biotamentioning
confidence: 99%
“…However, these microplastics or nanoplastics are also released to the atmosphere, becoming airborne contaminants [55,86,89]. Indeed, a study shows contamination in working environments [33]. Workers in the synthetic textiles, flock and vinyl chloride (VC), or polyvinyl chloride (PVC) industries are potentially exposed to high concentrations of microplastics in the air during work [76].…”
Section: Damage and Diseases Caused By Plastic Micromaterials And Nanmentioning
confidence: 99%
“…Therefore, microplastic and nanoplastic contamination is everywhere [24]. Microplastics have been found in human stool [25] and humans can consume microplastics and nanoplastics through seafood [26][27][28][29][30] and water [31][32][33][34][35][36], etc. Whether plastics will harm our health is unclear; however, the potential consequences may affect the ecological functioning of the globe and future generations of organisms ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Karst aquifers are fractured limestone aquifers that are susceptible to surface water influence. One study showed microplastic concentrations of up to 15.2 particles/L in karst aquifers in Illinois (Panno et al ). The microplastic contamination co‐occurred with indicators of septic water influence such as triclosan and phosphate.…”
Section: Occurrence Datamentioning
confidence: 99%